Detection of Slag Inclusions and Degree of Roughness in Welded Joints by Application Approach: Deteksi Inklusi Terak dan Tingkat Kekasaran pada Sambungan Las dengan Pendekatan Aplikasi - Muhammad Aqdar Fitrah; Hermin Hardyanti Utami (Jurnal Sains dan Teknik Terapan, 2023)
Slag Inclusion is a defect that occurs in areas in the weld. This defect is in the form of slag (melting flux) that is in the welding. In this study, an experiment was conducted using a sample of SA 106 Grade B pipe, aiming to detect slag inclusion defects and evaluate the degree of roughness in GTAW (Gas Tungsten Arc Welding) and SMAW (Shielded Metal Arc Welding) combinations with an application-based approach. This approach uses a special application to automatically detect slag inclusion defects and measure the surface roughness level of the weld results. The research method involves collecting welding samples with a variety of relevant process parameters. The collected data were then analyzed qualitatively and quantitatively. The results achieved were that in the GTAW and SMAW combination welding there were Slag inclusion weld defects in the weld metal area in the fill pass layer, the size of the slag defects in welding was obtained with a defect depth value of 0.5 µm while for SEM testing and supported by the use of software produced an average roughness with value (Ra) 70.536 nm, roughness average root (Rq) 99.0837 nm, maximum height of roughness (Rt) 847. 170 nm, maximum valley depth of roughness (Rv) 313.262.)